Nilai Keadilan dalam Sistem Kewarisan Islam - Rifenta, Fadlih; Prayogo, Tonny Ilham (Fakultas Syariah IAIN Purwokerto, 2019)
In the context of inheritance, reform efforts by contemporary Muslim thinkers have so far not been able to significantly change the shadow of classical inheritance law in Islam. This condition is caused by the effect of the mindset of the society in their epistemology, which assumes that the distribution of inheritance must be equal. Of course, we cannot blame the public for their knowledge of Islamic inheritance law. The question that arises is why they are in a hurry to accept the equal distribution of inheritance without conducting a study based on Islamic law on inheritance. Thus, the biggest challenge for Islamic scholars and inheritance law experts today is how to find a comprehensive formulation of various theories of knowledge that can be accepted by everyone, so that Islamic inheritance law is not only a discourse, but is able to totally reflect a concrete concept. This paper seeks to reorient and rethink the inheritance law in the development of Islamic legal epistemology which is examined in conjunction with the Shari’a provisions, which contain the values of justice in terms of theology, economics, and social.